Structure-activity relationship of karrikin germination stimulants - Flematti, G.; Scaffidi, A.; Goddard-Borger, E.; Heath, C.; Nelson, D.; Commander, L.; Stick, R.; Dixon, Kingsley; Smith, S.; Ghisalberti, E. (American Chemical Society, 2010)
Karrikins (2H-furo[2,3-c]pyran-2-ones) are potent smoke-derived germination promoters for a diverse range of plant species but, to date, their mode of action remains unknown. This paper reports the structure-activity relationship of numerous karrikin analogues to increase understanding of the key structural features of the molecule that are required for biological activity. The results demonstrate that modification at the C5 position is preferred over modification at the C3, C4, or C7 positions for retaining the highest bioactivity. © 2010 American Chemical Society.